(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
In the digital era, stable and fast Internet service is compulsory. Since 2017, the XYZ Foundation Manado has built and utilized a data communication networks infrastructure based on the wireless networking standard. The infrastructure is intended to support administrative works, such as financial operations, and admission processes. Unfortunately, in recent times, there has been an increase in complaints from employees who use the infrastructure. Therefore, in this Community Partnership Program, a thorough audit and evaluation were carried out, to find the location of the problems experienced by users, so that later when making repairs, the funds disbursed could be right on target. Evaluation is carried out on the physical condition of the infrastructure, network traffic, and user habits. From the evaluatio, it was found that some equipment should be replaced, and the cable management must be restructured.